dSPACE DS1104 Based Real Time Implementation of Sliding Mode Control of Induction Motor - Aymen Omari; I. K. Bousserhane; A. Hazzab; B. Bouchiba (Institute of Advanced Engineering and Science, 2018)
In this paper, the design of a speed control scheme based on a total sliding mode control for Indirect Field Oriented of a three phase induction motor (IM) is proposed. Firstly, the indirect field oriented control is derived. Then, sliding mode control design is investigated to achieve a speed tracking objective under different load torque disturbance. Finally a dSPACE DS1104 R&D board is used to implement the proposed scheme. The experimental results released on 0.25 kW slip-ring IM show a high dynamic performance, fast transient response without overshot as well as a good load disturbances rejection response.